(3TQM WGT cHQi RGOIs - (3GdJQcj, CHh GdNjQ, WGTcHQj RGOg, YUGe GdOjf, CMeO Hf eUWai Hf Ndjd, (B968 (3g`s
(3ChdgG (B:s
(3GdMeO ddg GdPj dG eGfY dYWGFgabO cfJ cJHJ YOI ef GdSWhQ eY bdI GdHVGYI hcKQI GdaJhQ aj Yde GdefGVQI hGdBOGH hbO bUOJ TQMgG HYhf Gddg Gdedc GdhgGH , CMeOc Gddge jG eLjH s
(3BNQgG (B:s
(3hJGSYgG Cfg jfHZj Cf dG jMJSH GdefGXQ GdNUe MbjQG dGf GSJMbGQ GdNUe QHeG jDOj Edi UOhQ GdcdGe GdVYja Yf GdefGXQ ajchf SHH GdZdHI GdNUe GdVYja Ydjg (B...(3JeJs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B1\257s
(3cTa GdXfhf (B1/41s
(3eUOQ GbJfGA GdCUd (B:s
(3Ydj CejQjs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdadSaI hGdefWbs